Particle localization and hyperuniformity of polymer‐grafted nanoparticle materials. Issue 5 (23rd March 2017) - Chremos, Alexandros; Douglas, Jack F.
Abstract : Many of the unique properties of soft materials derive from the way the molecules localize from their packing interactions. Particle deformability allows new particle localization states at which the density fluctuations are greatly suppressed, like in crystals, while being disordered; such materials are called "disordered hyperuniform". A promising material with such properties is a liquid composed of polymer‐grafted nanoparticles that exhibits a reversible liquid‐gel transition. Abstract : The properties of materials largely reflect the degree and character of the localization of the molecules comprising them so that the study and characterization of particle localization has central significance in both fundamental science and material design. Soft materials are often comprised of deformable molecules and many of their unique properties derive from the distinct nature of particle localization. We study localization in a model material composed of soft particles, hard nanoparticles with grafted layers of polymers, where the molecular characteristics of the grafted layers allow us to "tune" the softness of their interactions. Soft particles are particular interesting because spatial localization can occur such that density fluctuations on large length scales are suppressed, while the material is disordered at intermediate length scales; such materials are called "disordered hyperuniform". We use molecular dynamics simulation to study a liquid composed of polymer‐grafted nanoparticles (GNP), which exhibit a reversible self‐assembly into dynamic polymeric GNP structures below a temperature threshold, suggesting a liquid‐gel transition. We calculate a number of spatial and temporal correlations and we find a significant suppression of density fluctuations upon cooling at large length scales, making these materials promising for the practical fabrication of "hyperuniform" materials.